LABOUR LAW IN FRONT OF DIGITAL ECONOMY CHALLENGES - Jašarević, Senad; Božičić, Darko M (Zbornik radova Pravnog fakulteta u Novom Sadu, 2022)
Digital technologies aren’t knocking on our doors, they are already in our homes. They have changed the way how we communicate, travel, how we do our shopping, using cars, listening music… and there are countless examples. But, they have changed the way how we work as well. Digital technologies make work easier, safer and work markets are more accessible. On the other hand, some of us do not enjoy so much in presence of digital technologies because they represent “job killers“ or potential for violation on privacy at work. These are just few of challenges for Labour law in new digital era.
Keywords: digital economy, labour law, lifelong learning, privacy at work, digital platforms